Impact of flavivirus vaccine-induced immunity on primary Zika virus antibody response in humans. - Stefan Malafa; Iris Medits; Judith H Aberle; Stephan W Aberle; Denise Haslwanter; Georgios Tsouchnikas; Silke Wölfel; Kristina L Huber; Elena Percivalle; Pascal Cherpillod; Melissa Thaler; Lena Roßbacher; et al. (Public Library of Science (PLoS), 2020)
Background Zika virus has recently spread to South- and Central America, causing congenital birth defects and neurological complications. Many people at risk are flavivirus pre-immune due to prior infections with other flaviviruses (e.g. dengue virus) or flavivirus vaccinations. Since pre-existing cross-reactive immunity can potentially modulate antibody responses to Zika virus infection and may affect the outcome of disease, we analyzed fine-specificity as well as virus-neutralizing and infection-enhancing activities of antibodies induced by a primary Zika virus infection in flavivirus-naïve as well as yellow fever- and/or tick-borne encephalitis-vaccinated individuals. Methodology Antibodies in sera from convalescent Zika patients with and without vaccine-induced immunity were assessed by ELISA with respect to Zika virus-specificity and flavivirus cross-reactivity. Functional analyses included virus neutralization and infection-enhancement. The contribution of IgM and cross-reactive antibodies to these properties was determined by depletion experiments. Principal findings Pre-existing flavivirus immunity had a strong influence on the antibody response in primary Zika virus infections, resulting in higher titers of broadly flavivirus cross-reactive antibodies and slightly lower levels of Zika virus-specific IgM. Antibody-dependent enhancement (ADE) of Zika virus was mediated by sub-neutralizing concentrations of specific IgG but not by cross-reactive antibodies. This effect was potently counteracted by the presence of neutralizing IgM. Broadly cross-reactive antibodies were able to both neutralize and enhance infection of dengue virus but not Zika virus, indicating a different exposure of conserved sequence elements in the two viruses. Conclusions Our data point to an important role of flavivirus-specific IgM during the transient early stages of infection, by contributing substantially to neutralization and by counteracting ADE. In addition, our results highlight structural differences between strains of Zika and dengue viruses that are used for analyzing infection-enhancement by cross-reactive antibodies. These findings underscore the possible impact of specific antibody patterns on flavivirus disease and vaccination efficacy.